Development of pipette tip gap closure migration assay (s-ARU method) for studying semi-adherent cell lines - Sanmukh, Swapnil Ganesh [UNESP]; Felisbino, Sérgio Luis [UNESP] (Springer Nature, 2018)
This work presents a pipette tip gap closure migration assay prototype tool (semi-adherent relative upsurge—s-ARU—method) to study cell migration or wound healing in semi-adherent cell lines, such as lymph node carcinoma of the prostate (LNCaP). Basically, it consists of a 6-well cover plate modification, where pipette tips with the filter are shortened and fixed vertically to the inner surface of the cover plate, with their heights adjusted to touch the bottom of the well center. This provides a barrier for the inoculated cells to grow on, creating a cell-free gap. Such a uniform gap formed can be used to study migration assay for both adherent as well as semi-adherent cells. After performing time studies, effective measurement of gap area can be carried out conveniently through image analysis software. Here, the prototype was tested for LNCaP cells, treated with testosterone and flutamide as well as with bacteriophages T4 and M13. A scratch assay using PC3 adherent cells was also performed for comparison. It was observed that s-ARU method is suitable for studying LNCaP cells migration assay, as observed from our results with testosterone, flutamide, and bacteriophages (T4 and M13). Our method is a low-cost handmade prototype, which can be an alternative to the other migration assay protocol(s) for both adherent and semi-adherent cell cultures in oncological research along with other biological research applications.
Keywords: Gap closure assay; LNCaP; Migration assay; Semi-adherent cell; Wound healing